Long-term remission of solitary bone plasmacytoma with minimal marrow involvement treated with only radiation therapy: A case report - Martinez-Cordero, Humberto; Seija, Daniela; Caro Perdomo, Sandra (Revista Colombiana de Cancerología, 2023)
Solitary bone plasmacytoma (SBP) and solitary extramedullary plasmacytoma (SEP) are rare entities characterized by localized proliferation of monoclonal plasma cells without systemic involvement. There is an intermediate stage between solitary plasmacytoma (SP) and non-secretory multiple myeloma (NSMM), known as SBP with minimal marrow involvement, which has an increased risk of progression to multiple myeloma (MM). The percentage of bone marrow infiltration by tumoral plasma cells must be less than 10% to be considered SBP with minimal marrow involvement instead of non-secretory and macro-focal MM. The present case highlights the challenging decision in a 42-year-old Hispanic male patient to offer only high-dose radiation therapy vs. systemic therapy with autologous bone marrow transplantation (ABMT), given the borderline infiltration of 10% in the bone marrow. Eventually, the patient was treated with only radiation therapy, remaining free of progression 3 years after diagnosis.